2016
DOI: 10.3389/fncel.2016.00183
|View full text |Cite
|
Sign up to set email alerts
|

Seizure-Induced Motility of Differentiated Dentate Granule Cells Is Prevented by the Central Reelin Fragment

Abstract: Granule cell dispersion (GCD) represents a pathological widening of the granule cell layer in the dentate gyrus and it is frequently observed in patients with mesial temporal lobe epilepsy (MTLE). Recent studies in human MTLE specimens and in animal epilepsy models have shown that a decreased expression and functional inactivation of the extracellular matrix protein Reelin correlates with GCD formation, but causal evidence is still lacking. Here, we used unilateral kainate (KA) injection into the mouse hippoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 46 publications
3
29
0
Order By: Relevance
“…Inhibition of TIMP1 restored the Nt cleavage of Reelin and reversed the KA-induced GCD (43). Furthermore, perfusion of the central fragment of Reelin could prevent this GCD (44). Although these studies demonstrate that GCD results from both the loss of Reelin-positive neurons and hindered proteolysis of Reelin after epileptic insult, the question still remains whether the recurrence of seizures in TLEs is due to GCD.…”
Section: Regulating Reelin Signalingmentioning
confidence: 93%
See 1 more Smart Citation
“…Inhibition of TIMP1 restored the Nt cleavage of Reelin and reversed the KA-induced GCD (43). Furthermore, perfusion of the central fragment of Reelin could prevent this GCD (44). Although these studies demonstrate that GCD results from both the loss of Reelin-positive neurons and hindered proteolysis of Reelin after epileptic insult, the question still remains whether the recurrence of seizures in TLEs is due to GCD.…”
Section: Regulating Reelin Signalingmentioning
confidence: 93%
“…Later studies were able to recapitulate the KA-induced GCD in rodent organotypic hippocampal slice cultures, which resulted in a rapid loss of Reelin-expressing hilar neurons. These organotypic hippocampal slice cultures also had elevated expression of the matrix metalloprotease (MMP) inhibitor, tissue inhibitor of MMP-1 (TIMP1), which led to reduced Nt cleavage and diffusion of Reelin (42)(43)(44). Inhibition of TIMP1 restored the Nt cleavage of Reelin and reversed the KA-induced GCD (43).…”
Section: Regulating Reelin Signalingmentioning
confidence: 99%
“…Biochemical and functional studies in model systems confirm that formation of a densely packed GC layer is dependent on proper Reelin signaling [58,62]. Further, human studies as well as genetic and chemical-induced mouse models of epilepsy showed association between reduced Reelin mRNA expression and GCD [13,16,22,24,27,42]; although there is discrepancy in the type of Reelin + cells (early-born Cajal-Retzius cells or late-born hilar interneurons) considered to be associated with GCD. Introduction of exogenous Reelin into kainate-injected mouse hippocampus was also reported to prevent GCD in mice [41].…”
Section: Similar Molecular Expression Patterns In Dispersed Gc Layersmentioning
confidence: 87%
“…Granule cell dispersion is commonly associated with HS in TLE, noted in 76% of surgical specimens in a recent series 17 . In the context of HS, seizure-induced loss of reelinsynthesising interneurons has been shown to initiate neo-migration of mature granule cells 18 .…”
Section: Diminished Granule Cell Migration In Sudepmentioning
confidence: 99%